India’s Trade Potential with SAARC Nations under SAFTA: Exploring India's Trade Potential with SAARC Nations (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In era of globalization, no country possesses all the facilities required for economic production of all goods and services consumed by its people. Therefore, to meet varied demands countries have to trade and maintain economic relations with other nations. REI (Regional Economic Integration) is also one of best way for increasing foreign trade especially among developing countries with the help of different measures such as trade liberalization and trade facilitation. It has been seen that RTA are proliferated in recent years due to slow progress of trade liberalization and trade facilitation through GATT and later by WTO (its successor). Therefore, countries entered into regional trade arrangement to get easy access and benefit of trade liberalization at small scale. It has been recognized that foreign trade can also play a significant role in economic integration of South Asian Region.